Studying The Role of Soil Texture and Spraying with The Nutrient Unigreen and Their Effect on The Growth of Dill Plants - Sultan, Sami Hamad (American Journal of Botany and Bioengineering, 2025)
A field experiment was conducted during the 2023–2024 growing season at the College of Medicinal and Industrial Plants, University of Kirkuk, to investigate the effect of soil texture and foliar application of the nutrient Unigreen on dill (Anethum graveolens L.) grown in pots. The experiment consisted of nine treatment combinations arranged in a factorial design with three replications. The first factor was soil texture with three types: sandy, clay loam, and loam. The second factor was foliar spray levels of Unigreen at three concentrations: half the recommended dose (½×), the recommended dose (1×), and double the recommended dose (2×). The recommended dose was 0.15 ml L of water. The results indicated that the loam soil combined with the recommended Unigreen dose (1×) produced the highest values for all studied traits. Plant height reached 89.36 cm, number of branches was 5.32 branches plant⁻¹, number of leaves was 152.4 leaves plant⁻¹, dry weight reached 12.42 g plant⁻¹, and chlorophyll content was 16.42 µg cm⁻². In contrast, the lowest values were recorded in sandy soil, where plant height was 72.15 cm, number of branches was 3.28 branches plant⁻¹, number of leaves was 113.9 leaves plant⁻¹, dry weight was 5.62 g plant⁻¹, and chlorophyll content was 12.35 µg cm⁻². Overall, the best performance was observed in loam soil with the recommended level of Unigreen application.